Contribución de las lenguas extranjeras al desarrollo de actitudes de tolerancia y respeto hacia el "otro" - Paricio Tato, Mª Silvina (Linguarum Arena, 2018)
The purpose of this article is to analyze the present state of Foreign Languages in Spain for Compulsory Secondary Education, putting the emphasis on the way in which it approaches the cultural component and the intercultural dimension. The text starts from the premise to consider the curriculum as a complex field in which diverse agents and spheres of social life converge, and that before its materialization in the reality of the classroom it is crossed by diverse phases of development. The analysis that we carried out corresponds to the curriculum prepared by the Administration which is the prescribed curriculum. In addition, it is argued that the foreign languages that are chosen to be included in the education system of a particular country are conditioned by an outer context, the relationship that maintains the countries in the international sphere. That outer context - in our case is the process of European construction and the globalización of the economic interchanges on world-wide scale which are exerting a decisive influence in the theoretical and methodological approaches adopted in the teaching of foreign languages, orienting one towards an intercultural and plurilingual dimension. It is important in this study to talk about the goal pursued by the European Union, that defends the importance of learning foreign languages and considers the linguistic wealth of Europe like a rich patrimony that must be preserved. Equally important is the reference to the way in which the intercultural approach appears within the Common European Framework of Reference for Languages: learning, teaching and evaluation (Cervantes Institute 2002), which is a kind of guide that indicates the directives and the directions to follow for the teaching and learning of languages in Europe, incorporating the more recent theoretical developments of the Didactics of the matter, developments that call for a more integrated teaching of language and culture. Assuming that the learning of foreign languages has a very important formative component that goes beyond the simple acquisition of a linguistic competence, an analysis of the official text centered in the sociocultural aspects and the intercultural conscience takes place. This analysis puts the accent on those fragments related to the development of tolerant attitudes and respect towards the “other”. The article concludes with brief notes directed to the teaching staff for the development of that intercultural dimension.